SINTESIS DAN KARAKTERISASI KOMPOSIT Fe3O4-ARANG AKTIF KULIT BUAH IHAU (Dimocarpus Longan var. malesianus Leenh.) SEBAGAI ADSORBEN METHYLENE BLUE - Azizah Fithri Ananda; Teguh Wirawan; Nanang Tri Widodo (Acta Chimica Asiana, 2025)
Research has been conducted on the synthesis and characterization of Fe3O4-active charcoal composite of ihau fruit peel (MAACI) as a methylene blue dye adsorbent. This research aimed to produce activated charcoal from ihau fruit peel (AACI) composited with magnetite (Fe3O4). AACI was prepared by carbonating Ihau fruit peel in a furnace at 425C for 1 hour and chemically activated by immersion in an HCl solution for 24 hours. The synthesis of MAACI was carried out using the coprecipitation method with FeCl3 • 6H2O and FeSO4 • 7H2O in a 3:2 ratio, followed by compounding with AACI. The MAACI was characterized by Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). The characterization results showed that the FTIR spectrum exhibits an absorption peak at a wavenumber of 586.36 cm-1, indicating the presence of the Fe-O group. SEM analysis revealed that the MMACI has denser pores and a coarser texture compared to activated charcoal. Meanwhile, XRD results showed a diffraction pattern that matches the characterization of magnetite (Fe3O4). The adsorption of methylene blue by MAACI yielded optimum results at a pH of 9 with a contact time of 45 minutes. The maximum adsorption capacity obtained was 8.7014 mg/g, and the adsorption process followed the Langmuir isotherm model. This adsorption takes place spontaneously, is endothermic and occurs physically.